The Effect of Breastfeeding on Food Allergies in Newborns and Infants - Zoi Koukou; Eleftheria Papadopoulou; Eleftherios Panteris; Styliani Papadopoulou; Anna Skordou; Maria Karamaliki; Elisavet Diamanti (MDPI AG, 2023)
Breastfeeding is the preferred method of infant feeding and its establishment is one of the primary goals for the infant. Allergic diseases are common in childhood, with increased morbidity. Food allergies are also associated with a strong negative impact on health-related quality of life and is a major public health problem. In addition, maternal exclusion of common allergens during pregnancy and/or lactation suggests that supplementation with regular cow's milk formula during the first week of life should be avoided. Breast milk contains many active immune factors, such as cytokines, inflammatory mediators, signaling molecules and soluble receptors, which may also reduce the risk of allergic disease. The prophylactic effects of breastfeeding have been the subject of many studies, some with weak evidence. In this narrative review, we aim to provide an up-to-date account of the effects of prophylactic breastfeeding on food allergy and other common allergies in infants and children up to 5 years of age. Colostrum in particular has been shown to be prophylactic against food allergy. The American Academy of Pediatrics cautions that the relationship between duration of breastfeeding and incidence of food allergy in early childhood is unclear. The protective role of breastfeeding has a positive effect on allergy prevention, which is opposed by the early introduction of solid foods, but larger studies are needed to confirm the evidence. There is evidence that breastfeeding is effective in providing partial protection to infants.